The Utilization of Palm Oil Mill Effluent Decanter Cake as an Organic Fertilizer on Edamame Type Soybean (Glycine max) - Made Deviani Duaja; Elis Kartika; Buhaira Buhaira; Danang Adil Asmoro (Agro Bali : Agricultural Journal, 2022)
Decanter cake is a solid waste from a palm oil mill with quite a lot of availability and has not been utilized optimally. This research aimed to utilize decanter cake (DC) palm oil mill solid waste as solid Fertilizer and liquid Fertilizer to increase the growth and yield of Edamame. The research design used was a Randomized Block Design (RBD) with a treatment of solid DC with liquid DC, namely solid DC 0 tons ha-1, 10 tons ha-1, and 15 tons ha-1, with liquid DC concentrations of 0 % and 100 %. The variables observed were the number of leaves, number of pods, weight of pods, and yield of Edamame per hectare. The results showed that the highest number of leaves was achieved at 15 tons ha-1 solid DC dose with 100 percent liquid DC concentration. Likewise, the highest number of pods and weight of pods was at a quantity of 15 tons ha-1 and had the same effect as a dose of 20 tons ha-1 with a 100 percent liquid DC concentration. The best edamame yields per hectare were achieved in 15-ton ha-1 solid DC and 100 percent liquid DC concentrations.